2010
DOI: 10.1007/s11033-010-0652-7
|View full text |Cite
|
Sign up to set email alerts
|

Common Familial Mediterranean Fever gene mutations in a Turkish cohort

Abstract: Familial Mediterranean Fever (FMF) is an autosomal recessive autoinflammatory disorder with the responsible gene of MEFV which primarily affects Jewish, Armenian, Turkish and Arab populations. The FMF gene (MEFV) has recently been cloned to chromosome 16 p, which encodes pyrin. In the present study, we enrolled 2,067 unrelated patients with the suspicion of FMF in Middle Anatolia between the years 2006-2009 and identified the 12 MEFV mutations. DNA was amplified by PCR and subjected to reverse hybridization fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 25 publications
9
42
0
3
Order By: Relevance
“…While exon 10 contains 4 principal mutations (M694V, V726A, M680I, M694I), exon 2 contains 1 mutations (E148Q). Pyrin/marenostrin encoded in MEFV gene plays a role in the regulation of the inflammation showing an autoregulator effect on leukocytes (20). In the study performed by Yilmaz et al, it was reported that in our country, 5 mutations including M694V, E148Q, M680I, V726I, M694I were common (21).…”
Section: Epidemiologymentioning
confidence: 85%
See 1 more Smart Citation
“…While exon 10 contains 4 principal mutations (M694V, V726A, M680I, M694I), exon 2 contains 1 mutations (E148Q). Pyrin/marenostrin encoded in MEFV gene plays a role in the regulation of the inflammation showing an autoregulator effect on leukocytes (20). In the study performed by Yilmaz et al, it was reported that in our country, 5 mutations including M694V, E148Q, M680I, V726I, M694I were common (21).…”
Section: Epidemiologymentioning
confidence: 85%
“…In the pediatric patients, the diagnosis is more comprehensive to avoid any delay. Genetic analysis is useful to confirm the diagnosis of FMF in the suspected patients who shows late-onset, atypical clinical symptoms without ethnic or familial history (20). However, mutation cannot be detected in some patients with FMF who responded to colchicine therapy (11).…”
Section: Diagnosis and Prognosismentioning
confidence: 99%
“…The total frequency of M680I was 20.7% in this study, and very similar to the frequency of mutations at E148Q (21.1%). While mutations at M680I are the third and fourth most frequently reported in studies from the Aegean region (Berdeli at al., 2011), they were the second and third most frequent in studies from Central Anatolia (Dundar et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…In another study performed by Dundar et al (29), the allele frequency was reported to be M694V 14.68%, M680I (G/C) 7.62%, E148Q 5.15%, and V726A 4.76%. In a study carried out on 153 FMF patients in Syria, the most prevalent mutations were in order of frequency, M694V (36.5%), V726A (15.2%), E148Q (14.5%), M680I (G/C) (13.2%), and M694I (10.2%) (30).…”
Section: M680i(g/mentioning
confidence: 88%